Risk perceptions and risk management strategies of insured and non-insured dairy farmers: A comparative study - KHAN, MOHD AMEER; CHANDER, MAHESH; BARDHAN, D (The Indian Journal of Animal Sciences, 2014)
This study was conducted to analyze the farmers’ perceptions of risk and risk management among the farmers who had insured and non-insured their dairy animals. The data originated from a questionnaire survey of insured (120) and non-insured (120) dairy farmers in Gorakhpur district of Uttar Pradesh. Farmers’ Socio-economic characteristics, risk perceptions and risk management strategies were documented. The average land holding, educational status and dairy farm experience of insured respondents was slightly larger than that of the non-insured dairy farmers. Epidemic livestock diseases, climate risk, marketing/sales risk, feed cost variability, Poor conception and delay in treatment/AI emerged as relevant sources of risk to the dairy farmers. The most relevant risk management strategy for the dairy farmers were vaccination of animals, having own agricultural land, having financial reserve, life insurance, livestock insurance and off farm employment. The intensity and domination of risk and risk management tool adopted by dairy farmers varied due to their personal perceptions of risk, socio-economic status of that farmer, farm type and institutional arrangements.